2013
DOI: 10.5152/ucd.2013.01
|View full text |Cite
|
Sign up to set email alerts
|

D1 versus D2 dissection in stomach carcinoma: evaluation of postoperative mortality and complications

Abstract: The D2 procedure was associated with significantly higher postoperative mortality, morbidity, and postoperative length of hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…Many factors affect prolonged duration of operation. Complicated surgical procedures result in longer duration of operation and increase the risk of morbidity (19). Procedural duration is generally prolonged in advanced tumor cases, but it does not always lead to EJA leakage.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors affect prolonged duration of operation. Complicated surgical procedures result in longer duration of operation and increase the risk of morbidity (19). Procedural duration is generally prolonged in advanced tumor cases, but it does not always lead to EJA leakage.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, GC patients treated with D2 lymphadenectomy also showed prolonged OS and DFS, which is consistent with the results of the above mentioned studies. However, D2 lymph node dissection might lead to higher postoperative mortality and morbidity [39]. Yarema et al claimed that D2 lymphadenectomy could improve the prognosis in European populations of GC patients, but only when the surgical quality of lymphadenectomy execution is adequate [40].…”
Section: Discussionmentioning
confidence: 99%
“…In Western society, including Turkey, gastric cancer is diagnosed in more advanced stages. Diagnosis in early stages is one of the most important factors affecting the treatment and survival of the disease [9].…”
Section: Introductionmentioning
confidence: 99%